Genetic mechanisms establishing thalamocortical connectivity : novel genes and a role for Semaphorin6B - Bahena-Bibollet, Olivia (Trinity College (Dublin, Ireland). Department of Genetics, 2015)
One of the main functions of the brain is to process information from the environment. All input to the neocortex passes through the thalamus in order to be handled. Therefore, proper connectivity between the thalamus and the neocortex is crucial. During brain development a staggeringly complex network of connections selfassembles between billions of neurons through a finely orchestrated series of stages. Extracellular proteins, known as guidance molecules, induce attractive or repulsive responses from extending axons leading them through their journeys towards their appropriate targets. Although different guidance molecules have been identified to date, it is speculated that many more are required to explain the observed complexity in brain connectivity.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.